2021
DOI: 10.1073/pnas.2025054118
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of ribozymes inside model protocells leads to faster evolutionary adaptation

Abstract: Functional biomolecules, such as RNA, encapsulated inside a protocellular membrane are believed to have comprised a very early, critical stage in the evolution of life, since membrane vesicles allow selective permeability and create a unit of selection enabling cooperative phenotypes. The biophysical environment inside a protocell would differ fundamentally from bulk solution due to the microscopic confinement. However, the effect of the encapsulated environment on ribozyme evolution has not been previously st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 115 publications
0
15
0
Order By: Relevance
“…This autocatalytic cycle may have driven the early evolution of aminoacyl-RNA synthetase ribozymes. In this context, it is noteworthy that in vitro selection and evolution experiments have produced multiple aminoacyl transferase ribozymes with distinct sequences and amino acid substrates, suggesting that ribozyme-catalyzed aminoacylation could have been a function that was relatively easy to evolve in the RNA world ( 38 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…This autocatalytic cycle may have driven the early evolution of aminoacyl-RNA synthetase ribozymes. In this context, it is noteworthy that in vitro selection and evolution experiments have produced multiple aminoacyl transferase ribozymes with distinct sequences and amino acid substrates, suggesting that ribozyme-catalyzed aminoacylation could have been a function that was relatively easy to evolve in the RNA world ( 38 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, compartmentalization provides protection against kleptoparasites. In fact, various studies on RNA-based systems have shown that compartments may also protect against other forms of parasitism. , In addition compartments can enhance the rate of evolutionary adaptation in directed evolution experiments . We already witnessed in our own experiments that parasites may emerge at early stages in the development of life (see above) …”
Section: The Next Stepsmentioning
confidence: 92%
“…46,47 In addition compartments can enhance the rate of evolutionary adaptation in directed evolution experiments. 100 We already witnessed in our own experiments that parasites may emerge at early stages in the development of life (see above). 87 Once compartmentalization has been achieved, the next and possibly final challenge will be to achieve Darwinian evolution of the resulting system in a meaningful way.…”
Section: ■ the Next Stepsmentioning
confidence: 99%
“…[ 108 ] In a recent article, it was shown that the encapsulation of ribozymes inside phospholipid compartments in bulk led to faster evolutionary adaptation compared to ribozymes free in solution. [ 179 ] Nonenzymatic primer extension inside fatty acid compartments was also reported. [ 180 ]…”
Section: Model Protocell Systemsmentioning
confidence: 99%